Longitudinal association between psychological distress and mask-wearing post COVID-19 among psychiatric outpatients in Japan - Kazuhiro Suzuki; Yuka Mizuno; Yusuke Arai; Keitaro Miyamura; Daimei Sasayama; Shinsuke Washizuka (PLoS ONE, 2025)
The COVID-19 pandemic significantly impacted psychological distress globally and led to widespread behavioral changes, including mask-wearing. Research shows that mask-wearing behavior may have psychological consequences. Infection control behaviors and psychological distress are expected to decrease as the pandemic subsides. However, the effect of these changes on patients with mental illnesses remains unclear. Hence, this study aimed to evaluate the impact of relaxed mask-wearing guidelines on psychological distress among psychiatric outpatients in Japan and its association with changes in mask-wearing behavior. It included 109 outpatients from a general hospital’s psychiatric department. Psychological distress was assessed using the General Health Questionnaire-12 at two time points: before and after the guideline change. Mask-wearing behavior was recorded through self-reports. Changes in psychological distress were analyzed using the Wilcoxon signed-rank test, and the association between changes in mask-wearing behavior and psychological distress was examined using multiple regression analysis, adjusting for preceding psychological distress, age, and gender. Among the 109 participants (12 with schizophrenia, 55 with mood disorders, 34 with anxiety disorders, and 8 with other conditions), a significant reduction in psychological distress was observed after the guideline relaxation (Cohen’s d = 0.344, p < 0.01). Outdoor mask-wearing decreased from 89% before the guideline change to 65% after the change. Changes in mask-wearing behavior were significantly associated with reduced psychological distress (β = 2.72, p < 0.01). Relaxed mask-wearing guidelines positively impacted psychological distress among psychiatric outpatients, with unmasking associated with improved mental health. Thus, the relaxation of public health measures can contribute to improved mental health among vulnerable populations. This study provides new insights into the psychological implications of mask-wearing policies in the post-COVID-19 society and informs strategies to support mental health in future public health crises.